THU0542 In Vitro Anti-Inflammatory Effects of Dexamethasone and Ctla4-Ig (ABATACEPT) Combined Treatment. (10th June 2014) - Cutolo, M.; Montagna, P.; Soldano, S.; Contini, P.; Villaggio, B.; Sulli, A.; Seriolo, B.; Brizzolara, R.
Abstract : Background: In rheumatoid arthritis (RA) the combination of glucocorticoids (GC) and the fusion protein CTLA4-Ig (abatacept) allows to obtain better clinical improvement than CTLA4-Ig monotherapy. Our recent data showed that CTLA4-Ig interact with the CD86 molecule and directly dowregulates RA synovial macrophages, inducing a reverse signaling upon the binding [1-3]. Objectives: In this study the anti-inflammarory effect of dexamethasone (DEX) alone or combined with CTLA4-Ig was evaluated in vitro on cultured human activated macrophages. Methods: THP-1 cells, activated into macrophages (PMA 0.05 μg/ml; 24 hrs), were cultured for 48 hrs with DEX (10 –7 M) alone, or combined with CTLA4-Ig (500 μg/ml). Cells untreated and treated with CTLA4-Ig alone, were used as controls. CD86 expression was evaluated by immunofluorescence (IF) and by flowcytometry (FACS) analysis. IL-1β, TNFα and IL-6 protein production was investigated at 48 hrs after treatments by immunocytochemistry (ICC) and western blot analysis (WB). In addition, cytokine gene expression was evaluated at 1 and 3 hrs after treatments by quantitative real time polymerase chain reaction (qRTPCR). Results: Qualitative IF of CD86 demonstrated a decreased expression on untreated macrophages after DEX treatment alone and, more prominently after DEX and CTLA4-Ig-combined treatment. Quantitative FACS analysis confirmed these results: DEX alone induced a reduction of CD86 expression on cells by 78% and DEX combined with CTLA4-Ig induced an evident CD86 decrease by 97%, compared to the untreated cells. ICC analysis showed a decrease in IL-1β and TNFα production in macrophages treated for 48 hrs with DEX alone (ns) or combined with CTLA4-Ig (p<0.05), compared to untreated cells. CTLA4-Ig alone also significantly reduced IL-1β and TNFα production (p<0.05). Otherwise, IL-6 production in macrophages treated for 48 hrs with DEX alone or combined with CTLA4-Ig resulted unchanged, compared to untreated cells. WB analysis confirmed these results obtained after 48 hrs of treatment. qRTPCR showed in macrophages treated with DEX alone or in CTLA4-Ig-combined treatment, after only 1 hr, a reduction for the expression of all assayed cytokine genes. CTLA4-Ig alone reduced IL-1β, TNFα and IL-6 expression at 3 hrs, but not at 1 hr from treatment. At 3 hrs from DEX and DEX plus CTLA4-Ig treatment, cells still showed a reduction limited to IL-1β and IL-6 gene expression. Conclusions: Both DEX and DEX plus CTLA4-Ig treatments, induce a reduction in CD86 expression and an anti-inflammatory effect on human activated macrophages, by decreasing both cytokine protein and gene expression. The results seem mainly due to the CTLA4-Ig/CD86 binding and also partially related to the genomic effects exerted by DEX on cytokine gene expression. Results might explain the improved clinical conditions observed in RA patients treated with CTLA4-Ig and GC (1, 4). References: Brizzolara R et al. Reumatismo. 2011;63(2):80-54. Cutolo M et al. Clin Exp Rheumatol. 2013;31(6):943-6. Bonelli M et al. Arthritis Rheum 2013;65(3):599-607. Cutolo M et al. Ann N Y Acad Sci 2010;1193:15-21 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2844